Faktor- Faktor Eksternal pada Peternak Sapi Potong yang Mengikuti Program AUTS di Kabupaten Sinjai,Propinsi Sulawesi Selatan - Syukur, Syamsinar; Musdalipah, Musdalipah; Sirajuddin, Sitti Nurani; Fitriani, Nur (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2021)
Abstract This study aimed to determine the external factors of beef cattle farmers who participated in the Cattle Livestock Business Insurance (AUTS) program in Tellulimpoe District, Sinjai Regency. This research was conducted in Tellulimpoe District, Sinjai Regency from November to December 2018. The population was all of the beef cattle farmers who participated in the AUTS program, namely 582 people. Slovin formula was used to determine the samples and 41 beef cattle farmers were taken as a result. Primary and secondary data were used as data sources. The data were analyzed descriptively with the assistance of tabulation. The results showed that the external factors of beef cattle farmers who participated in the cattle business insurance program were the market for livestock business, the ever-advancing technology in the field of animal husbandry, the availability of production-supporting facilities along with the availability of equipment, production-stimulants for farmers, and lastly, freight and transportation. Key words: characteristics; beef cattle farmers; insurance; cattle; external factors Abstrak Penelitian ini bertujuan mengetahui faktor eksternal pada peternak yang mengikuti program Asuransi Usaha Ternak Sapi di Kecamatan Tellulimpoe, Kabupaten Sinjai. Penelitian ini dilaksanakan di Kecamatan Tellulimpoe Kabupaten Sinjai pada Bulan November sampai Desember 2018. Populasi adalah semua peternak sapi potong yang mengikuti program AUTS yaitu 582 orang. Responden yang diambil sebagai sampel dengan menggunakan rumus Slovin diperoleh 41 orang peternak. Sumber data adalah data primer dan data sekunder. Data dianalisis secara deskriptif menggunakan bantuan tabulasi.Hasil penelitian menujunkkan factor eksternal peternak yang mengikuti program asuransi usaha ternak sapi yaitu pasaran untuk hasil usahaternak, teknologi yang senantiasa maju di bidang peternakan, tersedianya sarana dan peralatan produksi pendukung yang tersedia di tempat, perangsang produksi bagi peternak, pengangkutan dan transportasi. Kata kunci: karakteristik; peternak; asuransi; sapi; faktor eksternal